"No language other than German may be spoken in this class". : Language and Diversity in the German School System (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2021)
Over the past five years, all EU28 countries have faced the challenge of integrating a large number of migrants* into their social and educational systems, including many children and young people of school age with flight biographies. The EU action plan for the integration of third-country nationals formulates the pan-European claim to grant refugee children and young people equal access to the education systems of the individual EU states (European Commission, 2016). In view of this migration policy situation, the question of how to deal with migration-related, socio-economic, linguistic and/or cultural heterogeneity in schools is of particular importance, despite extensive research on diversity. Educational and social science research has so far produced various concepts for dealing with linguistic heterogeneity as an aspect of diversity in schools. While one discourse is determined by the need to value the multilingualism of students and its identity-stabilizing effect, other discourses take the position that the use of a language of origin or family language other than German can be detrimental to school and social integration (e.g. Dirim, 2016; Esser, 2006). This paper examines the educational policy and professional challenges with a focus on multilingualism that arise during the school integration of refugees or new immigrants without knowledge of the national language. To answer this question, teachers, principals and school social workers at three schools in y were interviewed in a qualitative study with the help of a semi-structured interview guide. The result is a picture of the diversity orientation at several school types with different patterns of action in dealing with linguistic diversity and the resulting implications for teacher training and school development.